Enhancing students’ performance - Muhsin, Sayyed Mohamed (SUN MEDIA CORPORATION SDN BHD (221220-K), 2024)
worrisome ‘new norm,’ especially post-pandemic, is that the students are whirled in the vicious circle of digital interfaces. They appear to be ‘busy for nothing’. I have conducted a survey among undergraduate students at the International Islamic University Malaysia (IIUM) to assess their awareness of their own challenges and to solicit potential solutions. The survey received 200 responses, with 124 female and 76 male participants. Participants were queried about methods through which educators could enhance students' classroom performance.